Fenomena kawin paksa dalam pandangan Islam: Mufassir, ahli Hadist, tokoh Islam - Ramadhania, Safrida (Maliki Interdisciplinary Journal, 2024)
This article contains many views related to the phenomenon of forced marriage from several scholars, ranging from scholars who are mufassir, scholars who are experts in hadith, and religious figures. Forced marriage itself is very interesting to discuss because many scholars have views on it. In this review, it was found that Islam strictly prohibits the practice of forced marriage, because a valid marriage in Islam must be based on the free will and consent of both parties. Overall, this article emphasizes that forced marriage is not in accordance with the values ​​of Islamic law which prioritize freedom, consent, and the welfare of individuals in marriage. This study is expected to enrich understanding of the issue of forced marriage in the context of Islamic law and contribute to efforts to overcome this practice in Muslim society.